A SOA-based medical diagnosis decision support system using the Bayesian theorem and web service technology - Chang, Chung C.; Lu, Hsueh-Ming (Journal of the Chinese Institute of Engineers, 2009)
This study employs the framework of web services in conjunction with the Bayesian theorem to construct a SOA-based medical decision support system for diagnosis. The purpose is to help users (physicians) with issues pertinent to medical diagnosis decisions. Users, through the system, key in available prior probabilities, and through computation based on the Bayesian theorem, obtain more accurate diagnosis. The process helps users enhance the quality and efficiency of medical decisions. On the other hand, features of web services enable this medical decision support system to offer more service platforms than the conventional one. Users will have access to the system whether they use Windows, Macintosh, Linux or any other platforms that connect with the Internet via HTTP. More important is the fact that after the system is complete, all web system developers will be able to access the system as a software element freely and quickly. This way, the goal of this study - to provide a medical diagnosis decision support tool and speedily integrate heterogeneous medical decision support systems can be effectively achieved.